Changes in mental state associated with prison environments: a systematic review. (18th November 2013) - Walker, J.; Illingworth, C.; Canning, A.; Garner, E.; Woolley, J.; Taylor, P.; Amos, T.
<x xml:space="preserve">Abstract</x> Objective To develop an understanding of the stability of mental health during imprisonment through review of existing research evidence relating physical prison environment to mental state changes in prisoners. Method A systematic literature search was conducted looking at changes in mental state and how this related to various aspects of imprisonment and the prison environment. Results Fifteen longitudinal studies were found, and from these, three broad themes were delineated: being imprisoned and aspects of the prison regime; stage of imprisonment and duration of sentence; and social density. Reception into prison results in higher levels of psychiatric symptoms that seem to improve over time; otherwise, duration of imprisonment appears to have no significant impact on mental health. Regardless of social density, larger prisons are associated with poorer mental state, as are extremes of social density. Conclusion There are large gaps in the literature relating prison environments to changes in mental state; in particular, high‐quality longitudinal studies are needed. Existing research suggests that although entry to prison may be associated with deterioration in mental state, it tends to improve with time. Furthermore, overcrowding, ever more likely as prison populations rise, is likely to place a particular burden on mental health services.